The Fractional CIO in SMEs: conceptualization and research agenda - Simon Kratzer; Andreas Drechsler; Markus Westner; Susanne Strahringer (Information Systems and e-Business Management, 2022)
We conceptualize the new phenomenon of the Fractional Chief Information Officer (CIO) as a part-time executive who usually works for more than one primarily small- to medium-sized enterprise (SME) and develop promising avenues for future research on Fractional CIOs. We conduct an empirical study by drawing on semi-structured interviews with 40 individuals from 10 different countries who occupy a Fractional CIO role. We derive a definition for the Fractional CIO, distinguish it from other forms of employment, and compare it with existing research on CIO roles. Further, we find four salient engagement types of Fractional CIOs offering value for SMEs in various situations: Strategic IT management, Restructuring, Rapid scaling, and Hands-on support. The results reveal similarities with existing CIO roles as well as novel insights concerning the different engagement types. Lastly, we propose a research agenda for the Fractional CIO field, based on four research themes derived from existing CIO research and insights from the interviews.
Keywords: 650; Fractional CIO; Virtual CIO; IT leadership; Part-time management; SMEs; Small businesses; Interim management